2021
DOI: 10.1002/ajmg.b.32861
|View full text |Cite
|
Sign up to set email alerts
|

Rare protein‐coding variants implicate genes involved in risk of suicide death

Abstract: Identification of genetic factors leading to increased risk of suicide death is critical to combat rising suicide rates, however, only a fraction of the genetic variation influencing risk has been accounted for. To address this limitation, we conducted the first comprehensive analysis of rare genetic variation in suicide death leveraging the largest suicide death biobank, the Utah Suicide Genetic Risk Study (USGRS). We conducted a single-variant association analysis of rare (minor allele frequency <1%) putativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
(78 reference statements)
1
9
0
Order By: Relevance
“…Four studies have assessed rare variants (Coon et al, 2013; DiBlasi et al, 2021; Monson et al, 2017; Tombácz et al, 2017), all focused on suicidal behaviors. The most recent rare variant approach identified five high‐impact rare variants associated with SD in the following genes: SNAPC1 , TNKS1BP1 , ADGRF5 , PER1 , and ESS2 (DiBlasi, Kang, & Docherty, 2021). SNAPC1 and PER1 had previously been implicated in SITB.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies have assessed rare variants (Coon et al, 2013; DiBlasi et al, 2021; Monson et al, 2017; Tombácz et al, 2017), all focused on suicidal behaviors. The most recent rare variant approach identified five high‐impact rare variants associated with SD in the following genes: SNAPC1 , TNKS1BP1 , ADGRF5 , PER1 , and ESS2 (DiBlasi, Kang, & Docherty, 2021). SNAPC1 and PER1 had previously been implicated in SITB.…”
Section: Resultsmentioning
confidence: 99%
“…This gene is not found in the discovered network, or in PEC Network Modules, or in relevant KEGG pathways ( Table S7 and Table 4 ). There are no previously reported associations with addiction or psychiatric traits, except one report of an association of the rare missense variant rs149197213 in exon 6 of this gene with suicide [ 66 ]. Despite this, although we did not consider ADGRF5 among the best functional candidate genes in the present study, further investigations are needed before the role of ADGRF5 in the pathogenesis of AD can be completely ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the Utah Suicide Genetic Risk Study (USGRS) biobank showed that among the sample of 2,672 suicide deaths, compared to non-suicide deaths, both PER1 (Period Circadian Regulator 1) and SNAPC1 (Small Nuclear RNA Activating Complex Polypeptide 1) genes show evidence of suicide risk in bipolar disorder and schizophrenia [ 37 ]. The PER1 protein is important for the maintenance of circadian rhythms in cells, and its deficiency in mice causes loss of rhythmic telomerase activities, TERT mRNA oscillation, and shortened telomere length [ 11 , 38 ].…”
Section: Discussionmentioning
confidence: 99%